An interesting case of masculine voice in a girl: A case report of 11 beta hydroxylase deficiency - Haritha Galla; M N Satya Vani (Indian Journal of Child Health, 2021)
A 7-year-old girl presented to our outpatient department (OPD) with masculine voice, hyperpigmentation of skin, and genital ambiguity. On clinical examination, she had hypertension, hyperpigmentation of skin, pubarche, clitoromegaly, and low-pitched voice. Karyotype was 46 XX and ultrasound showed bilateral enlarged adrenals, uterus, and ovaries. Hormonal workup revealed elevated levels of 17-?-hydroxyprogesterone, testosterone, 11-deoxycortisol, and deoxycorticosterone. Due to the presence of hypertension, genital ambiguity and elevated 11-deoxycortisol, a diagnosis of 11-?-hydroxylase deficiency variant of Congenital Adrenal Hyperplasia was made. The child was started on hydrocortisone and amlodipine after which her symptoms such as hyperpigmentation improved.